Cleavage of an RNA Model Compound by an Arylmercury Complex - Saleh Lange Yakubu; Ora Mikko; Lönnberg Tuomas (WILEY-V C H VERLAG GMBH, 2025)
A water-soluble arylmercury complex has been synthesized, and its ability to catalyze the cleavage of the phosphodiester linkage of the RNA model compound adenylyl-3 ',5 '-(2 ',3 '-O-methyleneadenosine) has been assessed over a pH range of 3-8.5 and a catalyst concentration range of 0-7 mM. In the presence of 1 mM catalyst, the observed pH-rate profile featured a new pH-independent region between pH 6 and 7, the catalyzed reaction being as much as eight times faster than the background reaction. At pH 7, the acceleration increased linearly from three- to 17-fold upon increasing the catalyst concentration from 1 to 7 mM. The linear dependence indicates a relatively low affinity of the catalyst for the substrate and, hence, the potential for considerable improvement on tethering to an appropriate targeting group, such as an oligonucleotide.